Inclusion as Revolution? Examining Representations at the Intersection of Gender and Disability in Pop Music - Krarup, Ida (Leviathan: Interdisciplinary Journal in English, 2024)
This article examines the inclusion and exclusion of disabled women in pop music by conducting a sociolinguistic article. Mintz (2020) argued that disabled women will always be excluded from pop music because they cannot conform to the postfeminist ideal of the strong independent woman or the normative postfeminist body. In my analyses of three music videos, I examine the validity of this thesis. As my analysis of Run the World (Girls) shows, disability is often erased from postfeminist media due to the ableism inherent in postfeminism. However, as I show in my analysis of Prototype disabled women can be portrayed as strong independent women, but this involves accepting the stigmatization of dependency and perpetuating ableism. Finally, in my analysis of Running Underwater, I argue that non-ableist representations of disabled women in pop music are possible, but it must involve deconstructing ableist ideas such as the paradigm of a normative body.